Intracranial Pressure Values Are Highly Variable After Cerebral Spinal Fluid Drainage. Issue 2 (April 2017) - Rogers, Michael; Stutzman, Sonja E.; Atem, Folefac D.; Sengupta, Samarpita; Welch, Babu; Olson, DaiWai M.
Abstract : ABSTRACT: Intracranial pressure (ICP) is often obtained via external ventricular drain (EVD) placement and is discussed as a key vital sign in neuroscience. Nurses are most often delegated the task of observing, adjudicating, and documenting ICP. Cerebrospinal fluid drainage requires that the transducer connected to the EVD is open to drain, prohibiting ICP monitoring. There are no recent data to support an evidence-based standard for the period an ICP waveform should be observed, after the EVD is clamped, to be able to adjudicate a value that represents the patient's status. Therefore, the purpose of this study is to determine the optimal period for which an EVD should be closed to obtain an accurate ICP value. In a sample of 30 subjects who received continuous ICP monitoring for 15 minutes, there was no universal pattern to ICP after clamping an EVD. The conditional probability of observing a patient's highest ICP, if ICP is observed for 5 minutes, is 0.0181. The conditional probability increased to 0.0402 if ICP is observed for 10 minutes. There were no instances of ICP elevation requiring intervention. The results suggest that at least 5 minutes of ICP monitoring is safe and is required to provide an ICP value that reflects true ICP.